การพัฒนากลยุทธ์การบริหารสู่ความเป็นเลิศของโรงเรียนมาตรฐานสากลระดับประถมศึกษา - ราตรี ศรีไพรวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of this research were as follows: 1) To study the current states and desirable states of the management strategies toward excellence of the world class-standard elementary school. and 2) To develop the strategies of the management toward excellence of the world class-standard elementary school. This research is the Descriptive Research which the data were gathered from the questionnaires. Descriptive statistics are used in the data’s analysis and PNImodified technique is used to analysis the demand’s priority . Educated experts operated the focus group to examine the strategies’ suitability.The research’s result showed that (1) The current state of school management in The worldclass-standard school were performed at the high level as a whole and every criteria category. In desirable situation, every criteria category is the highest as follow : Leadership. (4.17) 2) The Result (4.16) Strategies Planning (4.12) Customer Focus and Process Management (4.08) 5) Evaluation , Analysis and knowledge management and Workforce Focus (4.02) . And in desirable states were performed at the high level in every criteria as follow : : Leadership and the Result (4.65) , the Process Management (4.62) , Workforce Focus (4.61) , Strategies Planning (4.60), Customer Focus (4.58) , and Evaluation , Analysis and knowledge management (4.57). The average of the developing the strategies of the management toward excellence’s demand was 0.12 (PNI [subscript modified] = 0.12)as a whole. After considering individually , the indexes which should be developed were as follow: Workforce Focus (PNI [subscript modified] = 0.15), Evaluation , Analysis and knowledge management (PNI [subscript modified] = 0.14) ,and Process Management (PNI [subscript modified] = 0.13).2) The strategy of the management toward excellence of the worl dclass-standard elementary school composes of three strategies: 1) Workforce Engagement 2) Performance Management Improvement 3) Work System and Process Improvement and the twelve vice strategies as follow: 1) Career Planning 2 ) Mentoring System3 ) Community Participation in School Culture 4) Safety School5) Empowerment 6) Information System Development 7) Performance Management Improvement 8) Learning Network 9) Emergency Management 10) Stakeholder Participation11) Technology and Innovation and 12) Internal control System Improvement.